Growth effects of age-related productivity differentials in an ageing society: A simulation study for Austria - Helmut Hofer; Thomas Url (Institute for Advanced Studies (IHS), 2005)
We integrate age specific productivity differentials into a long-run neoclassical growth model for the Austrian economy with a highly disaggregated labor supply structure. We assume two life time productivity profiles reflecting either small or large hump-shaped productivity differentials and compute an average labor productivity index using three different aggregation functions: linear, Cobb-Douglas, and a nested Constant Elasticity of Substitution (CES). Model simulations with age specific productivity differentials are compared to a base scenario with uniform productivity over age groups. Depending on the aggregation function, the simulation results show only negligible or small negative effects on output and other macroeconomic key variables.
Keywords: O41; J11; E17; 330; age specific productivity; demographic change; model simulation; Sparen; Wirtschaftswachstum; Neoklassik; Simulation; Österreich; Alternde Bevölkerung